Heat transfer during laminar film condensation of saturated and superheated Freon - 12 - Van der Walt, J.(Johannes) (Stellenbosch : Stellenbosch University, 2012)
Thesis (Ph. D. (Ing.)) -- University of Stellenbosch, 1972.